Eruptive activity of the Santorini Volcano controlled by sea-level rise and fall - Satow, C; Gudmundsson, A; Gertisser, R; Ramsey, CB; Bazargan, M; Pyle, D; Wulf, S; Miles, AJ; Hardiman, M (Springer Nature, 2021)
Sea-level change is thought to influence the frequencies of volcanic eruptions on glacial to interglacial timescales. However, the underlying physical processes and their importance relative to other influences (for example, magma recharge rates) remain poorly understood. Here we compare an approximately 360-kyr-long record of effusive and explosive eruptions from the flooded caldera volcano at Santorini (Greece) with a high-resolution sea-level record spanning the last four glacial–interglacial cycles. Numerical modelling shows that when the sea level falls by 40 m below the present-day level, the induced tensile stresses in the roof of the magma chamber of Santorini trigger dyke injections. As the sea level continues to fall to −70 or −80 m, the induced tensile stress spreads throughout the roof so that some dykes reach the surface to feed eruptions. Similarly, the volcanic activity gradually disappears after the sea level rises above −40 m. Synchronizing Santorini’s stratigraphy with the sea-level record using tephra layers in marine sediment cores shows that 208 out of 211 eruptions (both effusive and explosive) occurred during periods constrained by sea-level falls (below −40 m) and subsequent rises, suggesting a strong absolute sea-level control on the timing of eruptions on Santorini—a result that probably applies to many other volcanic islands around the world.